Acquired deficiency of peroxisomal dicarboxylic acid catabolism is a metabolic vulnerability in hepatoblastoma - Wang, Huabo (J Biol Chem, 2021)
Metabolic reprogramming provides transformed cells with proliferative and/or survival advantages. Capitalizing on this therapeutically, however, has been only moderately successful because of the relatively small magnitude of these differences and because cancers may further adapt their metabolism to evade metabolic pathway inhibition. Mice lacking the peroxisomal bifunctional enzyme enoyl-CoA hydratase/3-hydroxyacyl CoA dehydrogenase (Ehhadh) and supplemented with the 12-carbon fatty acid lauric acid (C12) accumulate the toxic metabolite dodecanedioic acid (DDDA), which causes acute hepatocyte necrosis and liver failure. We noted that, in a murine model of pediatric hepatoblastoma (HB) and in primary human HBs, downregulation of Ehhadh occurs in association with the suppression of mitochondrial β- and endosomal/peroxisomal ω-fatty acid oxidation pathways. This suggested that HBs might be more susceptible than normal liver tissue to C12 dietary intervention. Indeed, HB-bearing mice provided with C12- and/or DDDA-supplemented diets survived significantly longer than those on standard diets. In addition, larger tumors developed massive necrosis following short-term DDDA administration. In some HBs, the eventual development of DDDA resistance was associated with 129 transcript differences, ∼90% of which were downregulated, and approximately two-thirds of which correlated with survival in numerous human cancers. These transcripts often encoded extracellular matrix components, suggesting that DDDA resistance arises from reduced Ehhadh uptake. Lower Ehhadh expression was also noted in murine hepatocellular carcinomas and in subsets of certain human cancers, supporting the likely generality of these results. Our results demonstrate the feasibility of C12 or DDDA dietary supplementation that is nontoxic, inexpensive, and likely compatible with more standard chemotherapies.